Rail vehicle impact analysis: The instable propensity of structural responses and the critical scenarios of structural failure. (March 2016) - Xue, Xiangdong; Smith, Roderick; Schmid, Felix; Robinson, Mark
In this paper, the authors investigate the characterisation of the structural collapse of steel-bodied rail vehicles and propose modifications to a cab structure for improved structural crashworthiness. This is a mechanical- and simulation-based investigation, comprising three parts: after a mechanical description of the impact forces and energy conservation in collisions between trains, the characteristics of rail vehicle structures are examined to identify structural weaknesses in the context of impact stability. This is followed by a computer simulation of a cab structure to validate the conclusions from the theoretical analysis and to demonstrate the effectiveness of the design modifications. Focusing on the correlation between structural characterisation and impact stability, the authors highlight the following three findings: first, rail vehicles have a propensity to be unstable in the vertical direction due to the asymmetrical geometry and unbalanced impact loads; second, high shear stresses tend to be generated at the top corners of the rear pillars of the door region, leading to a localised fracture tendency; and third, impact stability can be enhanced through structural modifications by adopting symmetric cross sections or enhancing the stiffness in the weak direction for asymmetric structures, i.e. achieving geometric symmetry or stiffness balance on impact. The findings result in a better understanding of the mechanisms in structural crushing and advance the research into passive safety of rail vehicles.